The Effects of High- vs. Low-Load Resistance Training on Strength and Hypertrophy: A Systematic Review. - Sergio L. Jim´énez-Saiz; Carlos Alix; Juan Del Coso; Carlos Balsalobre-Fernández (Federación Extremeña de Balonmano; University of Extremadura, 2023)
INTRODUCTION: Traditionally, it has been proposed that strength gains and muscle hypertrophy required distinct characteristics to be achieved with resistance training.  However, current evidence shows that the obtaining of improvements of strength and hypertrophy can be obtained with a single resistance training protocol. The purpose of this systematic review was to examine the existing body of literature pertaining to association between load during resistance training and their effects on strength gains and muscle hypertrophy. METHODOLOGY: Searches were conducted on Web of Science, PubMed/Medline, and Embase with no year restriction applied to the search strategy. Selected studies met the following inclusion criteria: (a) studies that included a combination of young and old males and females, with no known medical conditions or injuries; (b) including a resistance training with high-loads (≥60% of one-repetition maximum, 1RM) or low-loads (<60% 1RM); (c) the duration and frequency of the resistance training protocols was equal; (d) measurement of hypertrophy and/or strength gains induced by the training; (e) in English and published in peer-reviewed journals. RESULTS: A total of 24 studies were included in the review. Overall, the increase in muscle mass were similar for both high-load and low-load resistance training protocols. However, in 10 out of 24 studies, the gains in strength were significantly higher with the high-load resistance training when compared to the low-load protocol. CONCLUSIONS: The use of loads above ≥60% of 1RM during a resistance training induces higher gains in muscle strength while muscle hypertrophy is similar to resistance training with lower loads. This suggests that the use of high loads is recommended during resistance training with the aim of maximizing training adaptations.